2011
DOI: 10.1177/0091270010370846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Commonly Administered Agents and Genetics on Nebivolol Pharmacokinetics: Drug-Drug Interaction Studies

Abstract: Drug interactions are a significant clinical concern, particularly in patients with conditions such as heart disease and hypertension, in whom coadministration of multiple drugs is common. Nebivolol is a selective β(1)-blocker with vasodilatory properties approved for the treatment of hypertension. Drug-drug interactions were investigated when nebivolol was coadministered to subjects classified as poor CYP2D6 metabolizers and extensive CYP2D6 metabolizers who were receiving other drugs commonly administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
(39 reference statements)
3
11
0
3
Order By: Relevance
“…Steady-state coadministration of bupropion increased the peak plasma concentrations (C max ) of both nebivolol and its hydroxylated active metabolite (1.67 ± 0.69 vs. 3.80 ± 1.70 ng/ml and 0.68 ± 0.22 vs. 1.13 ± 0.38 ng/ml). In the second period of the study (test), when bupropion was administered concomitantly with the betablocker, elevated plasma concentrations of nebivolol were found to be 2.3-fold higher than in the first period (reference); when the beta-blocker was given alone, the result was similar to the outcomes reported after coad- ministration of nebivolol and other CYP2D6 inhibitors, that is, fluoxetine [26] and paroxetine [27] . Additionally, the AUC 0-t and AUC 0-∞ values for nebivolol were significantly different before and after bupropion multipledose treatment (AUC 0-t : 10.38 ± 10.53 vs. 72.49 ± 46.20 ng * h/ml; AUC 0-∞ : 12.10 ± 11.02 vs. 87.29 ± 57.49 ng * h/ ml).…”
Section: Discussionmentioning
confidence: 55%
“…Steady-state coadministration of bupropion increased the peak plasma concentrations (C max ) of both nebivolol and its hydroxylated active metabolite (1.67 ± 0.69 vs. 3.80 ± 1.70 ng/ml and 0.68 ± 0.22 vs. 1.13 ± 0.38 ng/ml). In the second period of the study (test), when bupropion was administered concomitantly with the betablocker, elevated plasma concentrations of nebivolol were found to be 2.3-fold higher than in the first period (reference); when the beta-blocker was given alone, the result was similar to the outcomes reported after coad- ministration of nebivolol and other CYP2D6 inhibitors, that is, fluoxetine [26] and paroxetine [27] . Additionally, the AUC 0-t and AUC 0-∞ values for nebivolol were significantly different before and after bupropion multipledose treatment (AUC 0-t : 10.38 ± 10.53 vs. 72.49 ± 46.20 ng * h/ml; AUC 0-∞ : 12.10 ± 11.02 vs. 87.29 ± 57.49 ng * h/ ml).…”
Section: Discussionmentioning
confidence: 55%
“…In light of all the aspects mentioned above, it should be noted that the extrapolation of the current results to hypertensive patients receiving a dosing regimen of repeated nebivolol and fluvoxamine administration can be viewed as debatable as it remains unknown whether the interaction might become clinically relevant when multiple-dose nebivolol is combined with multiple-dose fluvoxamine. A small amount of data can be found in the scientific literature regarding the correlation between plasma levels and clinical response to nebivolol, but according to Lindamood et al, clinically safe and well-tolerated levels of nebivolol alone were previously observed in PMs with a pharmacokinetic profile which included the following mean parameters: AUC 0-∞ 614 ng*h/mL and C max 9.2 ng/mL (12). In comparison to these values, the peak plasma levels and the AUC 0-∞ value obtained after nebivolol was administered with fluvoxamine were notably lower, which could explain the difficulty in revealing any clinical significance in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol is extensively metabolized by oxidation, __________________________________________ glucuronidation, hydroxylation and N-dealkylation, each metabolic pathway providing different metabolites (10,11). The hydroxylated and glucuronidated metabolites are considered pharmacologically active, which contributes to an equally similar clinical profile for both CYP2D6 phenotypes (12,13). As CYP2D6 is a polymorphic isoenzyme, extensive metabolizers (EMs) and poor metabolizers (PMs) exhibit different pharmacokinetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that most of the commonly used β-blockers are either metabolized by CYP2D6 or eliminated by renal excretion 3,[12][13][14][15][16][17][18][19] ; thus, an awareness of which commonly used antidepressants significantly inhibit CYP2D6 10,11,[20][21][22][23][24][25] will warn clinicians about the risk of a potential drug interaction. Table 3 also lists antidepressants that are mild inhibitors of CYP2D6 10,23,25,26,[29][30][31] ; these are probably associated with lower risk of CYP2D6 drug interactions at usual clinical doses.…”
Section: Other Antidepressants and Other β-Blockersmentioning
confidence: 99%